Hudson, Warren. Warren Hudson, Adams Cove - Baccalieu Trail Heritage Corporation (2005)
This interview is part of a series of filmed oral histories, collected in 2005 by the Baccalieu Trail Heritage Corporation, from over 40 elders who grew up in the area. The Baccalieu Trail Heritage Corporation is a not-for-profit organization dedicated to preserving, promoting and protecting the heritage of the Baccalieu Trail Region. This project includes memories of living and working in the area, going to school, children’s games, home remedies, the first modes of transportation, supernatural beliefs, traditional industries and calendar customs and celebrations. This interview is with Warren Hudson of Adams Cove, NL. The interviewer is Robin Baker. The camera was operated by Julia Harrington. The video was edited by Mike Ryan and Darrell Barrett.